2021
DOI: 10.1155/2021/5995008
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Facebook and Newspaper Advertising on Sales: A Comparative Study of Online and Print Media

Abstract: Marketing means the strategies and tactics an organization undertakes for attracting consumers to promote the buying or selling of a product or service. Active marketing is about receiving messages from potential buyers to create ways to influence their purchasing decisions. Advertising is one of the most prominent marketing strategies to promote products to consumers. It is well known that advertisement has a significant impact on the sale of certain goods or services. In this paper, we consider two mediums o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 33 publications
0
9
0
3
Order By: Relevance
“…Authors of the scientific papers [67][68][69] describe the methodology of the comparative approach. The scientists in [70] apply this approach in a plane of markets of various countries, while the scientists in [71]-as an element of modeling, [72]-base their approach on the principles of applying machine learning models.…”
Section: Methods Applied In the Researchmentioning
confidence: 99%
“…Authors of the scientific papers [67][68][69] describe the methodology of the comparative approach. The scientists in [70] apply this approach in a plane of markets of various countries, while the scientists in [71]-as an element of modeling, [72]-base their approach on the principles of applying machine learning models.…”
Section: Methods Applied In the Researchmentioning
confidence: 99%
“…Telecommunications have demonstrated that an informatics program has changed dramatically. Technological evolution occurred in tandem with growing safety concerns [36].…”
Section: Mobile Network Protection and Vulnerability Environment Evol...mentioning
confidence: 99%
“…Društveni mediji, odnosno platforme poput Facebook-a i Youtube-a omogućavaju brzo kreiranje i deljenje sadržaja od strane korisnika, pružajući im osećaj slobode i važnosti u izražavanju i mišljenju (Weinberg & Pehlivan, 2011). Imajući u vidu značaj marketinga u poslovanju svakog preduzeća i povezanosti potrošača sa proizvodom, svrsishodno je da preduzeća primenjuju strategije koje mogu uticati na odluku potrošača za kupovinu određenog proizvoda (Lin et al, 2021). U tom smislu, oglašavanje na društvenim mrežama, ima posebnu ulogu.…”
Section: Društveni Mediji I Društvene Mrežeunclassified
“…Rezultati istraživanja pokazuju da oglašavanje na društvenim medijima pozitivno utiče na prodaju određenih proizvoda ili usluga (Elrod & Fortenberry, 2020;Sciglimpaglia et al, 2020;Shen et al, 2016). Sa druge strane, nalazi jednog istraživanja pokazuju da je oglašavanje putem društvenih medija efikasnije od štampanih medija (Lin et al, 2021). Rezultati istraživanja sprovedenog u Pakistanu pokazuju da je marketing na društvenim mrežama značajno povezan sa namerom kupovine, kao i da angažovanje potrošača delimično posreduje u tome kako marketing na društvenim mrežama utiče na nameru potrošača za kupovinom (Husnain & Toor, 2017).…”
Section: Grafikon 1 Globalna Struktura Prihoda I Prognoze U Milijardama Američkih Dolara Prema Vrsti Oglašavanjaunclassified
See 1 more Smart Citation